Historical Memory Law: a tribute or a late retaliation? - Leila Bukharmedova (Ибероамериканские тетради)
The article deals with the background of the Historical Memory Law that was passed in 2007. It stirred up the Spanish society and caused ﬁerce debates which demonstrated how sensitive this issue is for the Spaniards and how controversial their attitude is towards the Francoist past of the country. At the same time the debate surrounding this issue often depended on political preferences and wasn’t built on the basis of scientiﬁc interest